Radiation Exposure during Cardiac Interventions in Congenital Heart Defects: A Multicenter German Registry Analysis 2012–2020 - Tengler, Anja; Michel, Jörg; Arenz, Claudia; Bauer, UIrike; Beudt, Jens; Horke, Alexander; Kerst, Gunter; Beckmann, Andreas; Hofbeck, Michael (The Thoracic and Cardiovascular Surgeon, 2025)
Background Interventional cardiac catheterizations have gained major importance in the treatment of congenital heart defects (CHDs). Since patients with CHDs frequently require lifelong medical care and sometimes subsequent invasive treatment, repeated radiation exposure during interventional procedures is a relevant issue concerning potential radiation-related risks. Therefore, a 9-year subanalysis on radiation data during interventional cardiac catheterizations from the German Registry for Cardiac Operations and Interventions in patients with CHDs was performed.Methods The German Registry for Cardiac Operations and Interventions in Patients with CHDs is a real-world, prospective all-comers database collecting clinical and procedural data on invasive treatment of CHDs. From January 2012 until December 2020, a total of 28,374 cardiac catheter interventions were recorded. For a homogeneous case mix and for obtaining comparable data, eight specified interventions were selected for detailed evaluation. The selected procedures were: atrial septal defect (ASD)/patent foramen ovale (PFO) occlusion, patent ductus arteriosus (PDA) occlusion, ventricular septal defect (VSD) occlusion, coarctation of the aorta (CoA) balloon dilatation and stent implantation, aortic valvuloplasty, pulmonary valvuloplasty, and transcatheter pulmonary valve implantation (TPVI). Data on radiation exposure included total fluoroscopy time (TFT), dose area product (DAP), and DAP per body weight (DAP/BW).Results The cohort accounted for 9,350 procedures, including 3,426 ASD/PFO occlusions, 2,039 PDA occlusions, 599 aortic and 1,536 pulmonary valvuloplasties, 383 balloon dilatations and 496 stent implantations for CoA, 168 VSD occlusions, and 703 TPVI. Six hundred and ten ASD/PFO procedures (17.8%) were performed without radiation. During the 9-year period, median annual TFT, DAP, and DAP/BW showed a continuous decrease while radiation burden correlated with intervention complexity: For ASD/PFO and PDA occlusion, aortic and pulmonary valvuloplasty as well as balloon dilatation of CoA the median DAP/BW was <20.0 μGy*m2/kg, while median values of 26.3 μGy*m2/kg and 31.6 μGy*m2/kg were noted for stent treatment of CoA and VSD closure, respectively. Radiation burden was highest in TPVI with a median TFT of 23.6 minutes, median DAP of 4,491 μGy*m2, and median DAP/BW of 79.4 μGy*m2/kg.Conclusion A decrease in radiation exposure was found in eight cardiac interventions from January 2012 to December 2020. Comparison with international registries revealed a good quality of radiation protection. The data underline the requirement of surveillance of radiation burden, especially in this patient group.
Keywords: congenital heart disease; CHD; pediatric; cardiac catheterization/intervention (including PCI); stents; database